Child development for early years students and practitioners - Neaum, Sally (Los Angeles SAGE/Learning Matters, 2013)
"This accessible guide to child development is written specifically for students of degrees and foundation degrees in Early Years, Early Childhood Studies and related disciplines and for early years practitioners. It introduces the context of child development, how we can develop an understanding of this development and how ealy years practitioners can support this in practice. It considers the biological/social debate, explores holistic development, examines factors affecting development and includes a chapter on reflective practice. This second edition has been updated to include new guidance for the revised Early Years Foundation Stage...This edition also includes a new chapter introducing a critique of developmentalism. Throughout, new case studies have been included and interactive activities have been enhanced."--from the publisher.
Includes bibliographical references (pages 169-172) and index
Keywords: Child development; Early childhood education; Child development -- Problems, exercises, etc; Early childhood education -- Problems, exercises, etc